E1a-dependent expression of adenovirus genes in OTF963 embryonal carcinoma cells: role of E1a-induced differentiation. - Nelson, C C (1990)
Some undifferentiated F9 embryonal carcinoma cells allow adenovirus genes to be expressed independently of the E1a oncogene normally required for their activation; this has been attributed to a cellular equivalent of E1a in F9 cells. However, transcription of all early genes was low in undifferentiated OTF963 embryonic carcinoma cells during the first 48 hr after infection with adenovirus type 5 (Ad5). Transcription then increased to about the level seen 16 hr after infection of cells induced to differentiate by retinoic acid (RA) (referred to as RA-dF9 cells), but this increase did not occur in cells infected by the E1a deletion mutant dl312. Addition of E1a in trans, or of RA, had no immediate effect on viral transcription in OTF963 cells, but viral transcription increased about 48 hr after these additions. Ad5 induced transcription of several differentiation-specific genes in OTF963 cells with about the same kinetics as their induction by RA. These genes were superinduced in RA-dF9 cells by cAMP or infection by adenovirus. We suggest the small amount of E1a produced early in infection of OTF963 cells activates cellular genes, some of which are differentiation specific and required for efficient transcription of viral genes, so that E1a both induces and is induced by differentiation. The simple hypothesis of a cellular equivalent to E1a does not adequately explain the complex interactions between viral and cellular genes in OTF963 embryonic carcinoma cells.